Healthcare workers’ satisfaction on sbar tool for handover in a private hospital - Lee Hua Yik; Raijah A. Rahim; Rosnida Abu Bakar (2019)
Nursing handover is indispensable and functions as information exchange, care continuity, and fundamental to safe and quality patient care. Healthcare workers conduct shift handover in a background of chaotic, frequent interruptions, within limited timeframe. Healthcare workers’ satisfaction on shift handover directly and indirectly affects the patient’s safety and standards of care. Aims: To explore satisfaction on the SBAR tool for handover among healthcare workers in a private hospital. Design: A descriptive cross-sectional study. Setting: A private, multispecialty hospital (84-bed capacity). Population and Sample: Purposive sample (n = 89) of nurses and PCAs working in all the departments participated with voluntary participation and anonymity ensured, at 72% response rate. Data Collection: Anonymous self-administered questionnaire (Handover Evaluation Scale) with 14-item of 7-point Likert-type scale were returned within a one-week timeframe. Data Analysis: Descriptive statistics on demographics with frequency, percentage, mean and standard deviations. Statistical (inferential) analyses were run on HES responses and correlation with demographic variables. Narrative comments to open-ended questions were analysed qualitatively by summarising key themes. Results: Healthcare workers are found to be satisfied with SBAR for handover, with total score of 71.64 (SD = 8.81) in the range of 14-98. Associations are discovered between certain demographics and respondents’ satisfaction. Key strengths and limitations of SBAR, and suggestions for improvements are collected and all the above discussed pertaining to implications. Conclusion: Healthcare workers are satisfied with the use of SBAR for handover. There are associations between demographics with SBAR satisfaction. Key strengths, limitations, and suggestions for improvement in relation to SBAR are discussed. (Abstract by authors)